Research status and future prospect of carbon capture technology using steel slag in the context of carbon neutrality - Lei AN; Xiaoyuan ZHANG; Yu LIU (工程科学学报)
As the world’s largest steel producer, China generates substantial amounts of steel slag byproducts during the steel-making process, posing serious threats to the ecosystem. In China, steel slag is mainly landfilled, which compromises soil and aquatic environments and results in the waste of potentially recyclable resources. The increasing production of steel slag has prompted government and public efforts to develop suitable treatment and disposal methods that minimize environmental impact. As an alkaline solid waste, steel slag not only offers favorable accessibility but also serves as a promising resource for high-value recycling. Owing to its abundant endogenous active components, such as Ca2+ and Mg2+, steel slag has the potential to be used as a functional material for carbon capture. In the context of achieving carbon neutrality, steel slag-based carbon capture presents an effective and promising approach to carbon reduction. This article systematically reviews the current status of steel slag treatment and recycling in China and analyzes the reaction mechanisms and key influencing factors in the carbon capture process of steel slag. Steel slag-based carbon capture is generally categorized into direct and indirect methods. Owing to low mass transfer efficiency and a slow reaction rate, direct carbon capture has low CO2 capture efficiency and is time-consuming, making it less suitable for large-scale applications. Indirect carbon capture is less dependent on high temperature and pressure and achieves better mass transfer efficiency, making it more promising for application compared with direct carbon capture. Additionally, a comprehensive analysis of the crucial factors influencing steel slag-based carbon capture technology is provided. In the case of indirect carbon capture, extensive research has focused on improving the extraction efficiency of metal ions through methods such as ultrasound, extractants, and milling. Dissolution efficiency of carbon dioxide in the liquid phase is equally critical. Therefore, measures that can effectively enhance CO2 solubility, such as micro/nanobubbles and the application of seawater, were proposed. Additionally, during steel slag-based carbon capture, the synergistic treatment of multiple wastes, such as cold-rolling wastewater and exhaust flue gas, is considered a feasible strategy due to its potential environmental and economic benefits. Specifically, cold-rolling wastewater and exhaust flue gas can serve as alternatives to tap water and CO2 sources, respectively, thereby reducing the economic and energy burdens associated with upstream transport and processing. The proposed “waste treated by waste” strategy could facilitate the synergistic disposal of multiple waste streams in the steel industry, offering theoretical and technological insights for sustainable steel slag management. Because the carbonization routes (i.e., direct and indirect carbonization) may influence the chemical composition of the final carbonated products, resource recovery strategies should be tailored to maximize economic potential. Accordingly, the resource utilization potential of carbonated products for different valorization strategies was analyzed. In summary, this study aims to promote the large-scale application of steel slag-based carbon capture and accelerate the steel industry transition toward low-carbon development.